Policy externalities and international trade agreements - Limão, Nuno (World Scientific Publishing Company Pte Limited, 2019)
"The book Policy Externalities and International Trade Agreements is a selection of published articles examining how policy externalities motivate and can be addressed by international trading institutions. The studies provide groundbreaking evidence of the role of international market power and policy uncertainty as motives for trade agreements and on the potential clash between preferential trade liberalization (e.g. European Union, NAFTA) and multilateral agreements (WTO). The studies presented in this book not only identify and estimate how different policies interact with each other and across agreements, but also examine how international trading institutions can be used to limit redistribution towards special interest groups and enforce better cooperation across issues, such as labor and the environment, and between developing and developed countries."--